Efeito da Atenção Primária à Saúde na Associação entre Multimorbidade e Utilização dos Serviços de Emergência - Lamonato, Larissa Carolina Xavier Lacerda (2024)
This study aimed to investigate the effect of Primary Health Care (PHC) on the association between multimorbidity and emergency service utilization among adults in Brazil. It is a cross-sectional study, based on national household data from the National Health Survey conducted in 2019. The study tapped into Poisson regression to assess emergency service utilization among individuals with multimorbidity. Additionally, it has implemented the evaluation of the interaction of variables such as Family Health coverage and orientation towards PHC in these associations. Regarding the main variables of the scope analyzed in this study, the prevalence of multimorbidity found was 31.2% (95%CI 30.9-31.5), Family Health coverage was 71.8% (95%CI 71.4-72.0), and low orientation of services towards PHC was 70% (95%CI 69.1-70.9). The outcome adopted here, which is the use of emergency services, had a prevalence of 2.0% (95%CI 1.9-2.0). Analyzing the prevalence of emergency service utilization among individuals with and without multimorbidity, it was observed that the prevalence was twice as high among those with multimorbidity (3.1; 95%CI 2.9-3.3) compared to those without this condition (1.4; 95%CI 1.3-1.5). However, it was observed that individuals with multimorbidity and Family Health coverage had a 20% lower prevalence of emergency service utilization than those with multimorbidity and without Family Health coverage (PR: 0.8; 95%CI 0.6-0.9). The association between emergency service utilization and the presence of multimorbidity was not modified by the assessment of the service as highly oriented towards PHC (p = 0.956). The study showed that PHC had a positive effect on the association between multimorbidity and emergency service utilization. However, the challenge imposed by multimorbidity on the healthcare system is evident. Therefore, further research on this topic is suggested to understand the impact of PHC on health outcomes in individuals with multimorbidity.